Exploring the use of continuously synthesised layered double hydroxides for the sorption of pharmaceuticals from wastewater - Johnston, Amy-Louise (2024)
Anthropogenic activities are resulting in significant pollution of global environmental waters, causing detrimental impacts to human and environmental health. Emerging contaminants (ECs) are one class of pollutants of which detection in the environment is rapidly growing, with adverse and often unknown effects. Pharmaceuticals, including antibiotics, fall within this class of pollutants, and their presence in the environment is additionally concerning due to their contribution to the spread of antimicrobial resistance. Current wastewater treatment technologies were never designed for the removal of ECs, therefore advanced wastewater treatment technologies need to be implemented. Sorption is a promising technology.